Linking ASI-Mobile Android-Based App on Mothers Attitude and Behavior on Exclusive Breastfeed (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Exclusive breastfeeding within the Palangka Raya municipality is far below target, on which 14,99% (2016) and 16,76% (2017), respectively. There were several primary health has the feeding bout, only cover 2,58%. Due to a lack of mothers knowledge, regarding beneficial and proper breastfeeding practices. Todays technology presumably has the advantages as promotional media. The study was aimed to quantify the android-based application, so-called ASI-Mobile, towards mothers attitude and behavior, on exclusive breastfeeding within Jekan Raya district, Palangka Raya Municipality, Central Kalimantan. The Research was conducted in March - October 2019, using a quasi-experimental design, and the sample was 60 pregnant women, in the third trimester period, over the Jekan Raya District areas. ASI-Mobile was subjected to 30 pregnant women, while others 30 mothers by counseling, the conventional promotion type. Purposive sampling was used, their socio-economic was collected, descriptive analysis was conducted. Bivariate analysis, Wilcoxon ranked test was used to analyzed the effect of the treatments. We've have found a significant link on ASI-Mobile application toward mothers attitudes (p-value 0.046) and behavior (p-value 0.018). We concluded that the ASI-Mobile, an android-base application, is more effective towards shifting mothers attitudes and behavior on exclusive breastfeeding within our study area.